Study on hydration characteristics and micromechanical properties of illite based on molecular dynamics - Mian Li; Zhangping Yan; Yang Xu; Qiuqi Chen; Yuhang Zhou; Xin Tang (PLoS ONE, 2026)
This study focuses on the water absorption process of illite, a heavy clay mineral of oil shale, and its related physical, chemical and mechanical properties. The interaction between water and illite molecules under different temperature, pressure and water saturation was studied by coupling molecular simulation. The changes and influence characteristics of basic physical properties (volume, density, expansion effect) and mechanical properties (elastic modulus, Poisson ‘s ratio, mechanical heterogeneity) of hydrated illite were analyzed. The results of molecular simulation show that the water absorption of illite mainly expands in the z direction of the crystal, the pressure can inhibit the expansion, and the temperature and water saturation promote the expansion. The interaction between oxygen atoms and potassium ions in water is more intense under pressure, and temperature and water saturation promote the diffusion of water molecules. The elastic modulus of illite increases with the increase of pressure and decreases with the increase of temperature and water saturation. The research results provide a theoretical basis for the stability evaluation of clay minerals in the fields of petroleum exploitation and geotechnical engineering, and reveal the microscopic mechanism of illite hydration degradation under multi-field coupling conditions.